PERAN PENYULUH PERTANIAN DALAM KELOMPOK TANI DI DESA MALENOS BARU KECAMATAN AMURANG TIMUR KABUPATEN MINAHASA SELATAN - Pinangkaan, Clara; Maweikere, Audrey Julia Maria; Dumais, Joachim Noch Karel (AGRI-SOSIOEKONOMI, 2022)
Extension workers in farmer groups in Malenos Baru Village, East Amurang District, South Minahasa Regency. This research was conducted from August to September 2021. The data collected in this study were primary data obtained from extension workers and respondent farmers through interviews using questionnaires and secondary data obtained from literature from the relevant agency, the Agriculture Service of South Minahasa Regency. and the New Malenos Village Office and related literature. Sampling was done by purposive sampling (deliberately) as many as 15 samples. The results of this research showed that the role of agricultural extension workers in farmer groups in Malenos Baru Village, East Amurang District, South Minahasa Regency was categorized as quite good. This is proven based on the results of the study with the interpretation of the value of 62.88 percent which is included in the fairly good category.